Basic Nahwu Learning Problems at MTs Al-Irsyad East Cape Jabung - Saputra, M. Riadi; M. Syukron Maksum (Edumaspul: Jurnal Pendidikan, 2026)
This study aims to analyze the problems of basic nahwu learning in students of MTs Al-Irsyad Tanjung Jabung Timur and the efforts of teachers in overcoming them. Nahwu as one of the important branches of learning Arabic is often considered a difficult, abstract, and boring material by students. These difficulties have an impact on the low understanding of Arabic sentence structure and weak ability to read Arabic texts. This study uses a mixed method approach with qualitative dominance through a sequential exploratory design. The research subjects consisted of 2 Arabic teachers, 1 madrasah head, and 48 grade VIII students. Data collection techniques use observation, interviews, learning difficulty questionnaires, documentation, and diagnostic tests. Data analysis is carried out through data reduction, data presentation, conclusion drawn, and quantitative descriptive statistical strengthening. The results of the study show that the main problems of basic nahwu learning include low mastery of mufradat, weak understanding of the concept of i'rab, learning methods that are still teacher-centered, lack of learning media, and low student learning motivation. The average score of students' understanding of nahwu only reached 61.8 from the minimum completeness standard of 75. The novelty of this research lies in the analysis of basic nahwu problems based on the context of rural madrasas with limited learning resources and solution approaches through the integration of contextual examples of student life. This study recommends the application of nahwu learning that is more communicative, simple, and contextual so that students can more easily understand the structure of the Arabic language.